STUDI KOMUNITAS KARANG SCLERACTINIA SEBAGAI PENDUKUNG KEBERLANJUTAN PERIKANAN - Mohamad Sayuti Djau (LPPM Universitas Muhammadiyah Gorontalo, 2017)
This study aims to examine the community structure of scleractinia corals in natural substrates with the appearance of total cover (%), number of species, diversity index, dominance index, density. The method to see the condition of corals uses the quadrant transect technique at three sampling points. The sampling point is outside the coastal tourism area. The results showed that there were 43 genera of 180 species of scleractinian coral. Percentage cover shows that at th e point of two percent coral cover is 40%. The level of density and diversity in each transect at the three points is relatively the same. For dominance, the colon indicates the lowest dominance value. Continuous monitoring of the structure of the Sleracti nia coral community in coastal tourism areas is very important, considering that this area is visited by many local tourists, as well as a fishing area